Sistem Pakar Diagnosis Penyakit Stunting pada Balita menggunakan Metode Forward Chaining - Farid Wajidi; Nahya Nur (Jurnal Informatika Universitas Pamulang, 2021)
Stunting is a condition that occurs in toddlers that fails to grow as a result of nutritional deficiencies so that the height or length of the child's body is not normal for his age. Malnutrition occurs from the moment the baby is in the womb and in the early stages of the baby is born, but the stunting condition is only apparent after the baby is two years old. Currently, the problem occurs a lack of maternal knowledge of the importance of child nutrition during the first 1000 days of life and poor sanitation of the daily environment. Therefore, an expert system is designed to diagnose stunting disease early in children. The method used in expert systems is forward chaining. Expert systems provide diagnostic output as well as user history information, solutions, and processing of user history data. The expert system developed is helpful to help people in diagnosing stunting diseases easily and quickly, where the accuracy system is equal to 91%.